3D TV and 3D Cinema - Mendiburu, Bernard (Routledge, 2012)
Helps you master the technical requirements of shooting 3D stereoscopic images. This title defines the concept of a professional 3D camera system and describes what features are required to make a successful unit to keep your production on schedule and on budget.